Mighty Jack and Zita the spacegirl - Hatke, Ben (Hatke, Ben. Mighty Jack, 2019)
Teaming up with new friend Zita the spacegirl, Jack and Lilly confront an army of dangerous giants and screeds ready to lay siege to Earth and determined to end all human life.